Rehabilitation of Maxillary Anterior Esthetics by Alveolar Distraction Osteogenesis With Immediate Implant Placement: A Case Report - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
Esthetic reconstruction of severe soft and hard tissue deficiencies is the utmost challenge in implant dentistry. To prevent postoperative bone resorption and to control the amount of hard and soft tissue volume, distraction osteogenesis followed by immediate implant placement has been proven to be a promising combined technique. The aim of this report is to introduce a treatment strategy to maintain anterior esthetics and to control hard and soft tissue volume in a case, treated with the combined technique of vertical alveolar distraction and immediate implant placement. An osteotomy was performed by the use of an oscillating saw. Cut alveolar segment was mobilized, and a distractor device was inserted in between the segments. During the activation and consolidation periods of distraction, anterior esthetics was provided with removable acrylic provisional crowns placed on the distractor's rod. In 2 weeks of distraction period, vertically 10 mm of new bony segment was obtained, and 2 weeks after the removal of distractor, maxillary incisors were extracted. Four dental implants were placed according to the immediate placement protocol. In osseointegration period, provisional restorations were fabricated on abutments to form harmonious gingival contours and to maintain maxillary anterior esthetics until the fabrication of final restorations. (Implant Dent 2010;19:468-476)
Keywords: implant; alveolar distraction; prosthetic rehabilitation; esthetics; PARTIALLY EDENTULOUS PATIENTS; DENTAL IMPLANTS; CLINICAL REPORT; RESTORATIONS; BONE